2018
DOI: 10.1182/bloodadvances.2017015073
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of vessel lining cells in normal spleens and their role in the pathobiology of myelofibrosis

Abstract: Key Points• SVECs support the development of hematopoiesis in MF.• LCs and SVECs each have distinct properties and functions that differ between normal and MF spleens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 48 publications
(51 reference statements)
3
16
0
Order By: Relevance
“…For instance, consistent with their known blood-tissue barrier to secure strict homeostasis of the microenvironment and tight control of trans-endothelial cellular migration and solute transport (Su et al, 2011;Sweeney et al, 2019), brain and testis ECs highly expressed genes involved in transport processes. ECs from liver and spleen upregulated genes involved in scavenging and immuno-regulation, in agreement with their known role in scavenging pathogens, dead cells, and molecules (Qiu et al, 2018;Seternes et al, 2002) and the fact that the spleen regulates immune responses against pathogens (Bronte and Pittet, 2013), and the liver is under constant threat of an invasion by intestinal pathogens into the circulation (Poisson et al, 2017). ECs from especially the lung highly expressed MHC class II genes, suggesting a role in immune surveillance (Goveia et al, 2020).…”
Section: Discussionsupporting
confidence: 63%
“…For instance, consistent with their known blood-tissue barrier to secure strict homeostasis of the microenvironment and tight control of trans-endothelial cellular migration and solute transport (Su et al, 2011;Sweeney et al, 2019), brain and testis ECs highly expressed genes involved in transport processes. ECs from liver and spleen upregulated genes involved in scavenging and immuno-regulation, in agreement with their known role in scavenging pathogens, dead cells, and molecules (Qiu et al, 2018;Seternes et al, 2002) and the fact that the spleen regulates immune responses against pathogens (Bronte and Pittet, 2013), and the liver is under constant threat of an invasion by intestinal pathogens into the circulation (Poisson et al, 2017). ECs from especially the lung highly expressed MHC class II genes, suggesting a role in immune surveillance (Goveia et al, 2020).…”
Section: Discussionsupporting
confidence: 63%
“…Here, we observed that SCARA5 was expressed predominantly in the white pulp of the human spleen, but also expressed by CD31‐positive endothelial cells in the splenic red pulp, but not by CD68‐expressing macrophages (Figure ). In a systematic characterization of CD45‐depleted and FACs purified human splenic microvascular endothelial cells, CD31 + CD34 − CD8α + littoral cells, have been previously demonstrated to express a series of scavenger receptors including stabilin‐1, stabilin‐2, the macrophage mannose receptor CD206, and SCARA5 by mRNA analysis . Consistent with this observation, both VWF and SCARA5 colocalized with CD8α expressing cells within the red pulp of the spleen in sinusoidal‐like structures (Figure A).…”
Section: Discussionsupporting
confidence: 62%
“…Although the human IHC analysis cannot definitively demonstrate if VWF/SCARA5 coexpressing cells are producing and/or clearing this VWF, our VWF infusion data suggest that at least a portion of the VWF observed in these cells has been endocytosed. Moreover, a previously published microarray analysis of total RNA from FACS‐isolated littoral cells did not identify VWF expression as being either significantly upregulated or downregulated when compared with a reference pool . It is therefore plausible that along with stabilin‐2 and possibly other receptors, expression of SCARA5 in the splenic sinusoids contributes to the clearance of VWF in humans.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations